Warthin's tumour in oral and maxillofacial regions: an 18-year retrospective study of 1084 cases in an eastern-Chinese population. Issue 7 (July 2018) - Xu, W.; Lu, H.; Zhu, Y.; Ruan, M.; Zhang, C.; Yang, W.; Liu, S.
Abstract: There is little information in the English-language literature regarding Warthin's tumour (WT) in the eastern-Chinese population. A large retrospective study (1084 primary tumours over a period of 18 years) was carried out to investigate the clinicopathological features (patients' gender, age and tumour location) of these tumours in this population. A total of 994 (91.7%) patients were male and 90 (8.3%) were female, with a male/female ratio of 11:1. The mean age was 56.48 years (range 20–89 years), with a peak incidence in the fifth to seventh decade (82.1%). The favorite primary site of the tumour was the parotid gland ( n = 1055), followed by intra-/peri-parotid lymph nodes ( n = 13), upper neck ( n = 10), submandibular gland ( n = 4) and upper lip ( n = 1). Multifocal WTs arose in 9.5% (103 patients) of cases whereas bilateral multifocal WTs were found in 0.65% (seven patients). In 24 (2.2%) patients, WT were found to coexist with other different types of neoplasm synchronously. The most common subtype of metaplasia was the squamous metaplasia (166/250, 66.4%). The usual treatment measure is (bilateral) superficial parotidectomy and the patients should be followed long term, in view of possible metachronous WT, even after prolonged time intervals.